Active learning of eutectic phase diagram in engineering courses - Erika Figueiredo Hehnes; Paula Carolina de Souza; Júlio César Dutra (The Journal of Engineering and Exact Sciences)
The present article shows a new strategy used to cover phase diagrams for undergraduate mechanical engineering students. It is based on active learning in which students are required to investigate experimentally three different eutectic alloys by using X-ray diffraction and metallography. The first technique allows students to use Rietveld analysis to obtain the mass fraction of the present phases and they must compare their results with those obtained theoretically whilst the second one is used to characterize those phases and measured their area fractions. From these results, they can also compare them with those obtained theoretically, but considering the density of different phases. The results have shown that students understood more clearly concepts such as the lever rule, and the very interpretation of phase diagram: the liquidus and solidus curve and finally the eutectic point.